LEMBAGA ADAT PASITABE DI KABUPATEN LUWU TIMUR (1992-2011) - kulyasin, kulyasin (Universitas Hamzanwadi, 2018)
AbstractBased on the results of the study showed that the Pasitabe Customary Institution was born as a result of the upheaval that occurred in South Sulawesi. In the decade 50 to 60 which made conditions and situations very unsafe for some people of South Sulawesi, especially in Tana Luwu, most of the people consisted of sub-ethnic . For this reason, the sub ethnic groups in Tana Luwu also referred to the Padoe Tribe, Karunsi'e and Tambe'e exodus to other places. A series of meetings have been held to achieve the goal of forming a unitary group between the Padoe, karunsi'e, and Tambe tribes, namely in 1962 in Taliwan, the second meeting in 1984 in Pakatan and the third meeting took place in Wawondula in the same year as the establishment of the Institute Pasitabe custom formally by consensus. The development period of the Pasitabe Customary Institution began itself in 1992 where this year Pasitabe has officially declared itself as an Adat Institution, and cultural preservation that has been carried out to date provides positive results by giving education to the younger generation and always making it an ancestral civilization should be guarded. Pasitabe Customary Institutions influence several aspects of life, both social, cultural and political, in the social aspect Pasitabe has succeeded in restoring indigenous peoples' self-confidence. Culture and customary re-living and enthusiasm in participating in politics are very large. Because based on the findings that have been obtained, it is suggested that the government pay more attention to what customary institutions are better related to communal land and local cultural preservation.Customary Institutions, Pasitabe, Cultural Impacts, Social, Politics